Analisis sikap tanggung jawab siswa kelas III sekolah dasar pada pembelajaran PKn materi hak dan kewajiban - Maria Balpi Rutika; Idam Ragil Widianto Atmojo; Matsuri Matsuri (Didaktika Dwija Indria, 2025)
Education is a key pillar in the advancement of a nation and plays a crucial role in the development of human life. This research is important because it addresses students' sense of responsibility in PKn (Civic Education) learning, which is essential for students and serves as a minimum standard in the learning process. The study was conducted with third-grade teachers and students at SD Negeri Totosari on the topic of rights and obligations for the 2023/2024 academic year. The method used in this research is descriptive qualitative research. Data were collected through observation, interviews, questionnaires, and documentation. Once the data were gathered, analysis was performed using the interactive analysis model by Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. Data validity was ensured through source triangulation, technique triangulation, and time triangulation. The study developed five indicators of students' sense of responsibility: awareness of participating in learning, completing tasks and duties, accepting consequences of actions taken, being active in learning, and being focused and consistent. Based on the research findings and discussion, it can be concluded that instilling a sense of responsibility in students through face-to-face PKn learning, as reflected in their understanding and concrete actions, has been observed and needs to be maintained and enhanced.